Cross-sectional UK survey of advanced practice physiotherapy: characteristics and perceptions of existing roles. (2nd July 2021) - Rath, Lucy; Faletra, Agostino; Downing, Nick; Rushton, Alison
Abstract : Background/aims: Few studies have investigated the characteristics of advanced practice physiotherapy in the UK to evaluate current context and implementation. The aim of this study was to understand how advanced practice physiotherapy is implemented in the UK. Methods: A cross-sectional online descriptive national questionnaire was developed, using a previous survey and literature, comprising 33 closed, Likert-scale and open questions. Data analysis was undertaken using frequencies and thematic analysis. All 646 members of the Advanced Practice Physiotherapy Network were invited to participate. Results: A total of 142 (22% response) reported 13 job titles; 40% had experienced ≥1 title change; most (50.7%) preferred 'advanced practice physiotherapist'. High level job satisfaction was identified but barriers prevent fulfilment of the four advanced practice physiotherapy pillars: clinical practice, leadership and management, education and research. High level clinical skills and facilitating patient pathways were key to role differentiation. Problems included lack of support, inconsistency between responsibility and reward, and no consistent framework for advanced practice physiotherapy roles. Conclusions: Advanced practice physiotherapists are largely satisfied, but significant variation exists in titles and implementation of roles. A consistent advanced practice physiotherapy framework is required.